Motoric Cognitive Risk Syndrome: Predictor of Dementia and Age-Related Negative Outcomes - Chhetri, Jagadish K.; Chan, Piu; Vellas, Bruno; Cesari, Matteo (Frontiers in Medicine, 2017)
Cognitive disorders represent a leading cause of disability in the aging population, of which dementia has the highest global burden. Early signs of dementia such as slow gait and memory complaints are known to present well before the overt manifestation of the disease. Motoric cognitive risk (MCR) syndrome characterized by the simultaneous presence of gait disturbances and memory complaints in older subjects has been proposed to study the close interactions between the physical and cognitive domains as well as a possible approach to identify individuals at increased risk of dementia. In addition, studies have shown MCR as a predictor of other negative outcomes in older adults, including disability, falls and death. However, the concept of MCR is still in its early stage and approach to the syndrome is still not well established. This review aims to put together the various aspects of MCR syndrome including its pathophysiology,diagnosis, epidemiology, and relationship with other geriatric conditions.